Digital Marketing sebagai Strategi Peningkatan Omzet Penjualan dalam Perspektif Etika Bisnis Islam: Studi Kasus Helny Shop Majalengka - Maesyaroh, Ucu Siti; Suryaman, Maman (Masyarakat Ekonomi Syariah Bogor, 2024)
Business development is so rapid. This encourages business people to be smart in attracting consumers to increase their sales. One way is to implement a marketing strategy through social media. This research aims to determine digital marketing strategies for increasing sales turnover at Helny Shop Majalengka, and to determine the perspective of Islamic Business Ethics regarding the use of digital marketing to increase sales turnover at Helny Shop Majalengka.This research is field research with qualitative descriptive methods, data sources from primary data and secondary data, and data collection techniques using observation, interviews, and document methods. From this research it was found that, firstly, digital marketing was carried out by Helny Shop Majalengka to increase sales turnover, namely reducing business promotion costs with a high level of efficiency, being able to provide information about the products offered, having an attractive appearance on social media, playing a role in communicating between business owners and consumer. secondly, from the perspective of Islamic Business Ethics at Helny Shop Majalengka, namely prioritizing four things that are key success factors in business management by the characteristics exemplified by the Prophet Muhammad. Namely Siddiq, Amanah, Fathanah, Tabligh. The results of this research are that the digital marketing carried out by Helny Shop Majalengka is considered effective by utilizing various features on social media such as Facebook. However, the owner of Helny Shop Majalengka must understand more about digital marketing and must understand the features of the Instagram application to further increase sales turnover. From the perspective of Islamic business ethics, Helny Shop Majalengka has implemented the Prophet's business principles, namely, Siddiq, Amanah, Fathanah, Tabligh.